2003
DOI: 10.1046/j.1360-0443.2003.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Sporting activity and drug use: alcohol, cigarette and cannabis use among elite student athletes

Abstract: As a whole, practising sports as an elite student-athlete can be considered as correlated negatively with cigarette, alcohol and cannabis use. Nevertheless, this relationship depends on the kind of sport practised as well as the level of competition, and further research is needed to understand specific elite athletes' motives for use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
3
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 21 publications
8
96
3
11
Order By: Relevance
“…They have suggested that sport contributes to prevention through mechanisms such as reducing stress and anxiety, increasing selfesteem, decision-making power, resistance to other people's insistence, improving the image of the individual and knowing more about the destructive effects of drugs. In contrast to this group, some other groups introduced a number of other sports activities as a risk factor for smoking, drugs and alcohol abuse, and found that competitive culture and pressure to succeed could provide basis for such high-risk behaviors (8,(14)(15)(16)(17)(18)(19). Despite previous studies in the field of sport, this question still remains that whether there is a difference between sports activity in terms of teamwork and outside sports activities or not.…”
Section: Introductionmentioning
confidence: 71%
“…They have suggested that sport contributes to prevention through mechanisms such as reducing stress and anxiety, increasing selfesteem, decision-making power, resistance to other people's insistence, improving the image of the individual and knowing more about the destructive effects of drugs. In contrast to this group, some other groups introduced a number of other sports activities as a risk factor for smoking, drugs and alcohol abuse, and found that competitive culture and pressure to succeed could provide basis for such high-risk behaviors (8,(14)(15)(16)(17)(18)(19). Despite previous studies in the field of sport, this question still remains that whether there is a difference between sports activity in terms of teamwork and outside sports activities or not.…”
Section: Introductionmentioning
confidence: 71%
“…Some research has demonstrated that team sport members drink significantly more than members of individual sports (O'Brien & Lyons, 2000;Peretti-groups (sports considered to be individual in the current study) reported the highest prevalence of alcohol consumption. To further complicate matters, Ford (2007) found that alcohol consumption in men's soccer was low, yet by contrast in women's soccer it was high.…”
Section: Discussionmentioning
confidence: 92%
“…Yeme bozuklukları kadınlarda erkeklere göre 3 ila 8 kat daha yüksek bulunmuştur (Miller, Barnes, Sabo, Melnick & Farrell, 2002b). Fakat bu oran sporcularda, sporcu olmayanlara göre daha fazladır (Peretti-Watel, 2003). Genç sporcular, özellikle düşük vücut ağırlığının avantaja dönüştüğü sporlarda, performanslarını arttıracak vücut kompozisyonuna ulaşma baskısıyla daha büyük risk altındadırlar.…”
Section: Sporla Ilişkili Beslenme Bozukluklarıunclassified